STRATEGI PEMBERDAYAAN MASYARAKAT MELALUI PENGEMBANGAN DESA WISATA KAMPOENG LAMA - Ayu Anggraini Tambunan; Agus Purwoko; Wahyudi Rambe; M. Irvanni Bahri (ITB AAS Indonesia Surakarta, 2024)
Community empowerment has long been a primary focus in the tourism industry. Empowering local communities in the development of tourist villages should contribute to the overall well-being of the community. Denai Lama Village is a potential tourist village suitable for development and can serve as a platform for local community empowerment, enhancing positive aspects and providing benefits to the community. This study aims to analyze the empowerment of the Denai Lama Village community through the Kampoeng Lama tourist village. The research employs a descriptive methodology with a qualitative approach. Data collection techniques include field observations, interviews, and documentation. Data analysis is conducted through data reduction, data presentation, conclusion drawing, and verification. The findings of this study lead to the conclusion that the development of the Kampoeng Lama tourist village in Denai Lama Village has become a platform for community empowerment, providing positive benefits in social, cultural, and economic aspects. The community also utilizes local wisdom as the main attraction in the Kampoeng Lama tourist village. Community empowerment is carried out by focusing on capacity building, the role and initiative of the community as subjects or actors, enhancing the position and quality of community involvement/participation in tourism development, and increasing the positive benefits of tourism development for social, economic, and cultural welfare. This tourist village has fulfilled the 4A components (attraction, accessibility, amenity, ancillary) as requirements for tourism development.